Framework for action to support livestock Development - Ehui, Simeon K.; Shapiro, Barry I. (Ethiopian Society of Animal Production, 1995)
This paper addresses issues related to the role that livestock research can play in strategies that make up this framework for action, and especially its effective linkage with technology transfer efforts. The experience that ILRI brings to these discussions is mainly from Africa. Topics covered in this paper include current state of research, livestock research policy environment, sectoral and macro policy effects on livestock research impact, research strategies to promote livestock Development goals, linking research and technology transfer and where the needed resources will come from.